Ecological paving stone and preparation process thereof
By using construction waste and fly ash as fillers, combining unsaturated polyester and epoxy resin, and using 5-chloro-2-methyl-4-isothiazoline-3-one to form a composite inhibitor with copper ions, the solution is solved The problem of insufficient impact, wear and antibacterial properties of floor stone paving materials is insufficient, and better anti-slip and environmentally friendly floor stone paving materials are achieved.
Patent Information
- Application Number
- CN202411341096.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
AI Technical Summary
The existing floor stone paving materials have shortcomings in impact resistance, wear resistance, anti-slip performance and anti-bacterial properties, especially in rainy and humid environments, which are prone to moss and have poor anti-slip performance.
Use construction waste and fly ash as filler, combine unsaturated polyester and bisphenol A-type epoxy resin as bonding materials, and pass 5-chloro-2-methyl-4-isothiazoline-3-one with copper As a composite inhibitor, ions are fixed by chelating the chelating agent to form quaternary ammonium salts, improving impact, wear resistance and antibacterial properties.
It significantly improves the impact resistance, wear resistance and antibacterial properties of floor paving, effectively inhibits moss growth, enhances anti-slip performance, and reduces the loss of copper ions to the environment.
Smart Images

Figure CN119241132A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to an ecological floor paving stone and a preparation process thereof. Background Art
[0002] Traditional paving stones are mainly made of cement, aggregates and other raw materials. They have the advantages of high strength and not easy to deform, and are widely used in road construction projects in many fields such as municipal administration. Aggregates, as one of the main raw materials, are obtained by mining natural ores. However, the large-scale mining of natural ores has seriously damaged natural resources and ecosystems, which is not conducive to the protection of the ecological environment. Therefore, the preparation of ecological paving stones based on recyclable materials such as construction waste and industrial by-products has received widespread attention.
[0003] Chinese patent CN102863186B discloses an ecological slag artificial stone brick and a preparation method thereof. The ecological slag artificial stone brick has a layered integrated structure consisting of a base layer and a surface layer. The surface layer includes natural stone powder, cement and nano-silica sol. The base layer is steel slag concrete with a porous structure. The addition of steel slag reduces the use of natural stone and has good ecological performance. However, cement is used as a bonding material, and the impact strength and wear resistance need to be improved. In addition, in rainy and humid seasons, moss and harmful microorganisms are easily grown on the surface of the stone brick, and the anti-slip and antibacterial properties are poor. Summary of the invention
[0004] In view of the deficiencies in the prior art, the present invention provides an ecological paving stone to solve the problem that the impact resistance, wear resistance, anti-slip performance and antibacterial performance of the paving stone materials in the prior art need to be improved.
[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0006] A preparation process of ecological paving stones comprises the following steps:
[0007] Step 1: Mix EDTA (ethylenediaminetetraacetic acid) and thionyl chloride, react, and after the reaction is completed, filter and dry to obtain an EDTA chlorination product;
[0008] Step 2, dispersing the EDTA chlorination product in N,N-dimethylformamide, adding ethylenediamine dropwise, reacting after the addition is complete, cooling after the reaction is complete, filtering, recrystallizing the filtered precipitate, and drying to obtain the EDTA amidation product;
[0009] Step 3, dissolving 5-chloro-2-methyl-4-isothiazoline-3-one in ethanol to obtain a 5-chloro-2-methyl-4-isothiazoline-3-one solution;
[0010] Dissolve copper nitrate in ethanol to obtain a copper nitrate solution;
[0011] The EDTA amidation product is added to a 5-chloro-2-methyl-4-isothiazoline-3-one solution to react. After the reaction is completed, a copper nitrate solution is added, stirred, and rotary evaporated to obtain a composite inhibitor.
[0012] Step 4: Mix the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, silane coupling agent, and composite inhibitor, stir, add a curing agent, continue stirring, and obtain a mixture;
[0013] Step 5: Pour the mixture into the mold, vibrate and flatten it, heat and solidify it to obtain ecological paving stones.
[0014] Preferably, in step 1, the molar ratio of EDTA to thionyl chloride is 1:(8-12), and the reaction is carried out at a temperature of 65-75° C. until no gas is released.
[0015] Preferably, in step 2, the mass ratio of EDTA chlorination product to N,N-dimethylformamide is 37:(185-370), the molar ratio of EDTA chlorination product to ethylenediamine is 1:(4-5), and the reaction conditions are 90-100° C. for 1-1.4 h.
[0016] Preferably, in the step three, the mass ratio of the EDTA amidation product, the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the copper nitrate solution is 46:(300-350):(80-100), the mass ratio of 5-chloro-2-methyl-4-isothiazoline-3-one to ethanol in the 5-chloro-2-methyl-4-isothiazoline-3-one solution is 1:(5-10), and the mass ratio of copper nitrate to ethanol in the copper nitrate solution is 1:(5-10), the reaction conditions are to react at a temperature of 75-85°C for 10-15h, and the stirring conditions are to stir at room temperature at a stirring speed of 100-200r / min for 1-2h.
[0017] Preferably, in step 4, the mass ratio of the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, silane coupling agent, composite inhibitor and curing agent is (40-60):(20-30):(20-30):(10-20):(3-5):(5-10):(2-4), and the stirring condition is stirring at a stirring speed of 200-400 r / min for 30-60 min, and the condition for continued stirring is stirring at a stirring speed of 200-400 r / min for 3-5 min.
[0018] Preferably, the silane coupling agent includes γ-aminopropyltriethoxysilane.
[0019] Preferably, the curing agent in step 4 comprises benzoyl peroxide.
[0020] Preferably, in step 5, the vibration flattening condition is to vibrate at a frequency of 60-80 Hz for 5-10 min, and the heating curing condition is to cure at a temperature of 70-80° C. for 1-2 h.
[0021] The invention also discloses an ecological paving stone prepared by adopting the above-mentioned preparation process of the ecological paving stone.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] In the present invention, construction waste and fly ash, a byproduct of industrial production, are used as fillers, which reduces the ecological problems caused by the use of natural mineral materials and has good ecological performance; unsaturated polyester and bisphenol A type epoxy resin are used as bonding materials, and the two bonding materials have good compatibility and good bonding with the fillers, so that the prepared paving stones have high strength and good impact resistance. At the same time, due to the good wear resistance of the epoxy resin, the surface wear resistance of the paving stones is high;
[0024] In the present invention, 5-chloro-2-methyl-4-isothiazoline-3-one and copper ions are used as moss growth inhibition components, which can not only effectively inhibit and kill the growth of moss, prevent the paving stones from breeding moss in a humid environment, thereby improving the anti-slip performance, but also have good antibacterial performance; wherein, the copper ions are fixed by the chelating effect of the chelating agent, thereby reducing the heavy metal pollution caused by the loss of copper ions to water quality, soil, etc.; the chelating agent EDTA is modified, first reacts with thionyl chloride to form an acyl chloride group, and then the acyl chloride group reacts with ethylenediamine to obtain an amidation product, while the amide group is formed, an amino group and an imino group are introduced, and the tertiary amine group in the EDTA acyl chloride product molecule reacts with the chlorine atom in the 5-chloro-2-methyl-4-isothiazoline-3-one molecule, so that the chelated copper and the 5-chloro-2-methyl-4-isothiazoline-3-one are chemically bonded, and a quaternary ammonium salt is formed, thereby further improving the antibacterial performance;
[0025] The amino and imino groups introduced by the reaction of EDTA chlorination product with ethylenediamine can participate in the curing of epoxy resin, firmly combine the composite inhibitor with the binder in a chemically bonded manner, improve the stability of the moss growth inhibition component in the paving stones, and have a stable and lasting inhibitory effect on moss and harmful microorganisms. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The figure is a process flow chart of the preparation of the composite inhibitor of the present invention;
[0027] Figure 2 This is a process flow chart of the preparation of ecological paving stones in the present invention;
[0028] Figure 3 It is a bar chart showing the antibacterial performance test results of the ecological paving stones prepared in Examples 1-6 of the present invention and Comparative Examples 1-2. DETAILED DESCRIPTION
[0029] Example 1
[0030] This embodiment discloses a preparation process of ecological paving stones, comprising the following steps:
[0031] Step 1, EDTA and thionyl chloride are mixed, the molar ratio of EDTA to thionyl chloride is 1:8, react at 65°C until no gas is released, remove unreacted thionyl chloride by suction filtration, and dry in a vacuum drying oven at 50°C for 10 hours to obtain an EDTA chlorination product;
[0032] Step 2, disperse the EDTA chlorination product into N,N-dimethylformamide, the mass ratio of the EDTA chlorination product to N,N-dimethylformamide is 37:185, add ethylenediamine dropwise, the molar ratio of the EDTA chlorination product to ethylenediamine is 1:4, after the addition is completed, react at 90°C for 1.4h, after the reaction is completed, cool to room temperature, filter, add tetrahydrofuran 10 times the mass of the filtered precipitate to recrystallize the filtered precipitate, and place the crystalline product in a 50°C vacuum drying oven and dry for 10h to obtain an EDTA amidation product;
[0033] Step 3, dissolving 5-chloro-2-methyl-4-isothiazoline-3-one in ethanol, wherein the mass ratio of 5-chloro-2-methyl-4-isothiazoline-3-one to ethanol is 1:5, to obtain a 5-chloro-2-methyl-4-isothiazoline-3-one solution;
[0034] Dissolving copper nitrate in ethanol, wherein the mass ratio of copper nitrate to ethanol is 1:5, to obtain a copper nitrate solution;
[0035] The EDTA amidation product was added to the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the mixture was reacted at 75°C for 15 hours. After the reaction was completed, a copper nitrate solution was added, and the mass ratio of the EDTA amidation product, the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the copper nitrate solution was 46:300:80. The mixture was stirred at room temperature and a stirring speed of 100 r / min for 2 hours, and ethanol was removed by rotary evaporation at 50°C to obtain a composite inhibitor.
[0036] Step 4: Mix the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyltriethoxysilane, and composite inhibitor, stir at a stirring speed of 200 r / min for 60 min, add benzoyl peroxide, and stir at a stirring speed of 200 r / min for 5 min to obtain a mixture;
[0037] The mass ratio of crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyl triethoxysilane, composite inhibitor, and benzoyl peroxide is 40:20:20:10:3:5:2, and the particle size of the crushed construction waste is 5-10 mm.
[0038] Step 5: Pour the mixture into a mold, vibrate at 60 Hz for 10 minutes to flatten the mixture, and cure at 70°C for 2 hours to obtain ecological paving stones.
[0039] Example 2
[0040] This embodiment discloses a preparation process of ecological paving stones, comprising the following steps:
[0041] Step 1, EDTA and thionyl chloride are mixed, the molar ratio of EDTA to thionyl chloride is 1:12, react at 75°C until no gas is released, remove unreacted thionyl chloride by suction filtration, and dry in a vacuum drying oven at 50°C for 10 hours to obtain an EDTA acyl chloride product;
[0042] Step 2, dispersing the EDTA chlorination product into N,N-dimethylformamide, the mass ratio of the EDTA chlorination product to N,N-dimethylformamide is 37:370, adding ethylenediamine dropwise, the molar ratio of the EDTA chlorination product to ethylenediamine is 1:5, after the addition is completed, reacting at 100°C for 1h, after the reaction is completed, cooling to room temperature, filtering, adding tetrahydrofuran 10 times the mass of the filtered precipitate to recrystallize the filtered precipitate, and placing the crystalline product in a 50°C vacuum drying oven and drying for 10h to obtain an EDTA amidation product;
[0043] Step 3, dissolving 5-chloro-2-methyl-4-isothiazoline-3-one in ethanol, wherein the mass ratio of 5-chloro-2-methyl-4-isothiazoline-3-one to ethanol is 1:10, to obtain a 5-chloro-2-methyl-4-isothiazoline-3-one solution;
[0044] Dissolving copper nitrate in ethanol, wherein the mass ratio of copper nitrate to ethanol is 1:10, to obtain a copper nitrate solution;
[0045] The EDTA amidation product was added to the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the mixture was reacted at 85°C for 10 hours. After the reaction, a copper nitrate solution was added, and the mass ratio of the EDTA amidation product, the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the copper nitrate solution was 46:350:100. The mixture was stirred at room temperature and a stirring speed of 200 r / min for 1 hour, and ethanol was removed by rotary evaporation at 50°C to obtain a composite inhibitor.
[0046] Step 4: Mix the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyltriethoxysilane, and composite inhibitor, stir at a stirring speed of 400 r / min for 30 min, add benzoyl peroxide, and stir at a stirring speed of 400 r / min for 3 min to obtain a mixture;
[0047] The mass ratio of crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyl triethoxysilane, composite inhibitor, and benzoyl peroxide is 60:30:30:20:5:10:4, and the particle size of the crushed construction waste is 5-10 mm.
[0048] Step 5: Pour the mixture into a mold, vibrate at 80 Hz for 5 minutes to flatten the mixture, and cure it at 80°C for 1 hour to obtain ecological paving stones.
[0049] Example 3
[0050] This embodiment discloses a preparation process of ecological paving stones, comprising the following steps:
[0051] Step 1, EDTA and thionyl chloride are mixed, the molar ratio of EDTA to thionyl chloride is 1:10, react at 75°C until no gas is released, remove unreacted thionyl chloride by suction filtration, and dry in a vacuum drying oven at 50°C for 10 hours to obtain an EDTA chlorination product;
[0052] Step 2, dispersing the EDTA chlorination product into N,N-dimethylformamide, the mass ratio of the EDTA chlorination product to N,N-dimethylformamide is 37:220, adding ethylenediamine dropwise, the molar ratio of the EDTA chlorination product to ethylenediamine is 1:4.2, after the addition is completed, reacting at 100°C for 1h, after the reaction is completed, cooling to room temperature, filtering, adding tetrahydrofuran 10 times the mass of the filtered precipitate to recrystallize the filtered precipitate, and placing the crystalline product in a 50°C vacuum drying oven and drying for 10h to obtain an EDTA amidation product;
[0053] Step 3, dissolving 5-chloro-2-methyl-4-isothiazoline-3-one in ethanol, wherein the mass ratio of 5-chloro-2-methyl-4-isothiazoline-3-one to ethanol is 1:6, to obtain a 5-chloro-2-methyl-4-isothiazoline-3-one solution;
[0054] Dissolving copper nitrate in ethanol, wherein the mass ratio of copper nitrate to ethanol is 1:6, to obtain a copper nitrate solution;
[0055] The EDTA amidation product was added to a 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the mixture was reacted at 80°C for 12 hours. After the reaction was completed, a copper nitrate solution was added, and the mass ratio of the EDTA amidation product, the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the copper nitrate solution was 46:310:84. The mixture was stirred at room temperature and a stirring speed of 150 r / min for 1.5 hours, and ethanol was removed by rotary evaporation at 50°C to obtain a composite inhibitor.
[0056] Step 4: Mix the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyltriethoxysilane, and composite inhibitor, stir at a stirring speed of 300 r / min for 45 min, add benzoyl peroxide, and stir at a stirring speed of 300 r / min for 4 min to obtain a mixture;
[0057] The mass ratio of crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyl triethoxysilane, composite inhibitor, and benzoyl peroxide is 44:22:22:12:3.4:6:2.4, and the particle size of the crushed construction waste is 5-10 mm.
[0058] Step 5: Pour the mixture into a mold, vibrate at 70 Hz for 8 minutes to flatten the mixture, and cure at 75°C for 1.5 hours to obtain ecological paving stones.
[0059] Example 4
[0060] This embodiment discloses a preparation process of ecological paving stones, comprising the following steps:
[0061] Step 1, EDTA and thionyl chloride are mixed, the molar ratio of EDTA to thionyl chloride is 1:10, react at 75°C until no gas is released, remove unreacted thionyl chloride by suction filtration, and dry in a vacuum drying oven at 50°C for 10 hours to obtain an EDTA chlorination product;
[0062] Step 2, dispersing the EDTA chlorination product into N,N-dimethylformamide, the mass ratio of the EDTA chlorination product to N,N-dimethylformamide is 37:260, adding ethylenediamine dropwise, the molar ratio of the EDTA chlorination product to ethylenediamine is 1:4.4, after the addition is completed, reacting at 100°C for 1h, after the reaction is completed, cooling to room temperature, filtering, adding tetrahydrofuran 10 times the mass of the filtered precipitate to recrystallize the filtered precipitate, and placing the crystalline product in a 50°C vacuum drying oven and drying for 10h to obtain an EDTA amidation product;
[0063] Step 3, dissolving 5-chloro-2-methyl-4-isothiazoline-3-one in ethanol, the mass ratio of 5-chloro-2-methyl-4-isothiazoline-3-one to ethanol being 1:7, to obtain a 5-chloro-2-methyl-4-isothiazoline-3-one solution;
[0064] Dissolving copper nitrate in ethanol, wherein the mass ratio of copper nitrate to ethanol is 1:7, to obtain a copper nitrate solution;
[0065] The EDTA amidation product was added to the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the reaction was carried out at 80°C for 12 hours. After the reaction was completed, a copper nitrate solution was added, and the mass ratio of the EDTA amidation product, the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the copper nitrate solution was 46:320:88. The mixture was stirred at room temperature and a stirring speed of 150 r / min for 1.5 hours, and ethanol was removed by rotary evaporation at 50°C to obtain a composite inhibitor;
[0066] Step 4: Mix the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyltriethoxysilane, and composite inhibitor, stir at a stirring speed of 300 r / min for 45 min, add benzoyl peroxide, and stir at a stirring speed of 300 r / min for 4 min to obtain a mixture;
[0067] The mass ratio of crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyl triethoxysilane, composite inhibitor, and benzoyl peroxide is 48:24:24:14:3.8:7:2.8, and the particle size of the crushed construction waste is 5-10 mm.
[0068] Step 5: Pour the mixture into a mold, vibrate at 70 Hz for 8 minutes to flatten the mixture, and cure at 75°C for 1.5 hours to obtain ecological paving stones.
[0069] Example 5
[0070] This embodiment discloses a preparation process of ecological paving stones, comprising the following steps:
[0071] Step 1, EDTA and thionyl chloride are mixed, the molar ratio of EDTA to thionyl chloride is 1:10, react at 75°C until no gas is released, remove unreacted thionyl chloride by suction filtration, and dry in a vacuum drying oven at 50°C for 10 hours to obtain an EDTA chlorination product;
[0072] Step 2, dispersing the EDTA chlorination product into N,N-dimethylformamide, the mass ratio of the EDTA chlorination product to N,N-dimethylformamide is 37:300, adding ethylenediamine dropwise, the molar ratio of the EDTA chlorination product to ethylenediamine is 1:4.6, after the addition is completed, reacting at 100°C for 1h, after the reaction is completed, cooling to room temperature, filtering, adding tetrahydrofuran 10 times the mass of the filtered precipitate to recrystallize the filtered precipitate, and placing the crystalline product in a 50°C vacuum drying oven and drying for 10h to obtain an EDTA amidation product;
[0073] Step 3, dissolving 5-chloro-2-methyl-4-isothiazoline-3-one in ethanol, the mass ratio of 5-chloro-2-methyl-4-isothiazoline-3-one to ethanol is 1:8, to obtain a 5-chloro-2-methyl-4-isothiazoline-3-one solution;
[0074] Dissolving copper nitrate in ethanol, wherein the mass ratio of copper nitrate to ethanol is 1:8, to obtain a copper nitrate solution;
[0075] The EDTA amidation product was added to the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the reaction was carried out at 80°C for 12 hours. After the reaction was completed, a copper nitrate solution was added, and the mass ratio of the EDTA amidation product, the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the copper nitrate solution was 46:330:92. The mixture was stirred at room temperature and a stirring speed of 150 r / min for 1.5 hours, and ethanol was removed by rotary evaporation at 50°C to obtain a composite inhibitor;
[0076] Step 4: Mix the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyltriethoxysilane, and composite inhibitor, stir at a stirring speed of 300 r / min for 45 min, add benzoyl peroxide, and stir at a stirring speed of 300 r / min for 4 min to obtain a mixture;
[0077] The mass ratio of crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyl triethoxysilane, composite inhibitor, and benzoyl peroxide is 52:26:26:16:4.2:8:3.2, and the particle size of the crushed construction waste is 5-10 mm.
[0078] Step 5: Pour the mixture into a mold, vibrate at 70 Hz for 8 minutes to flatten the mixture, and cure at 75°C for 1.5 hours to obtain ecological paving stones.
[0079] Example 6
[0080] This embodiment discloses a preparation process of ecological paving stones, comprising the following steps:
[0081] Step 1, EDTA and thionyl chloride are mixed, the molar ratio of EDTA to thionyl chloride is 1:10, react at 75°C until no gas is released, remove unreacted thionyl chloride by suction filtration, and dry in a vacuum drying oven at 50°C for 10 hours to obtain an EDTA chlorination product;
[0082] Step 2: Disperse the EDTA chlorination product in N,N-dimethylformamide, the mass ratio of the EDTA chlorination product to N,N-dimethylformamide is 37:335, add ethylenediamine dropwise, the molar ratio of the EDTA chlorination product to ethylenediamine is 1:4.8, after the addition is completed, react at 100°C for 1h, after the reaction is completed, cool to room temperature, filter, add tetrahydrofuran 10 times the mass of the filtered precipitate to recrystallize the filtered precipitate, and place the crystalline product in a 50°C vacuum drying oven and dry for 10h to obtain an EDTA amidation product;
[0083] Step 3, dissolving 5-chloro-2-methyl-4-isothiazoline-3-one in ethanol, the mass ratio of 5-chloro-2-methyl-4-isothiazoline-3-one to ethanol being 1:9, to obtain a 5-chloro-2-methyl-4-isothiazoline-3-one solution;
[0084] Dissolving copper nitrate in ethanol, wherein the mass ratio of copper nitrate to ethanol is 1:9, to obtain a copper nitrate solution;
[0085] The EDTA amidation product was added to the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the reaction was carried out at 80°C for 12 hours. After the reaction was completed, a copper nitrate solution was added, and the mass ratio of the EDTA amidation product, the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the copper nitrate solution was 46:340:96. The mixture was stirred at room temperature and a stirring speed of 150 r / min for 1.5 hours, and ethanol was removed by rotary evaporation at 50°C to obtain a composite inhibitor;
[0086] Step 4: Mix the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyltriethoxysilane, and composite inhibitor, stir at a stirring speed of 300 r / min for 45 min, add benzoyl peroxide, and stir at a stirring speed of 300 r / min for 4 min to obtain a mixture;
[0087] The mass ratio of crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyl triethoxysilane, composite inhibitor, and benzoyl peroxide is 56:28:28:18:4.6:9:3.6, and the particle size of the crushed construction waste is 5-10 mm.
[0088] Step 5: Pour the mixture into a mold, vibrate at 70 Hz for 8 minutes to flatten the mixture, and cure at 75°C for 1.5 hours to obtain ecological paving stones.
[0089] Comparative Example 1
[0090] This comparative example discloses a preparation process of ecological paving stones, comprising the following steps:
[0091] Step 1, EDTA and thionyl chloride are mixed, the molar ratio of EDTA to thionyl chloride is 1:8, react at 65°C until no gas is released, remove unreacted thionyl chloride by suction filtration, and dry in a vacuum drying oven at 50°C for 10 hours to obtain an EDTA chlorination product;
[0092] Step 2, disperse the EDTA chlorination product into N,N-dimethylformamide, the mass ratio of the EDTA chlorination product to N,N-dimethylformamide is 37:185, add ethylenediamine dropwise, the molar ratio of the EDTA chlorination product to ethylenediamine is 1:4, after the addition is completed, react at 90°C for 1.4h, after the reaction is completed, cool to room temperature, filter, add tetrahydrofuran 10 times the mass of the filtered precipitate to recrystallize the filtered precipitate, and place the crystalline product in a 50°C vacuum drying oven and dry for 10h to obtain an EDTA amidation product;
[0093] Step 3, dissolving copper nitrate in ethanol, wherein the mass ratio of copper nitrate to ethanol is 1:5, to obtain a copper nitrate solution;
[0094] The EDTA amidation product was added to ethanol, and after mixing, a copper nitrate solution was added, and the mass ratio of the EDTA amidation product, ethanol, and copper nitrate solution was 46:250:80. The mixture was stirred at room temperature and a stirring speed of 100 r / min for 2 h, and the ethanol was removed by rotary evaporation at a temperature of 50° C. to obtain a composite inhibitor;
[0095] Step 4: Mix the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyltriethoxysilane, composite inhibitor, and 5-chloro-2-methyl-4-isothiazoline-3-one, stir at a stirring speed of 200 r / min for 60 min, add benzoyl peroxide, stir at a stirring speed of 200 r / min for 5 min, and obtain a mixture;
[0096] The mass ratio of crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyltriethoxysilane, composite inhibitor, 5-chloro-2-methyl-4-isothiazoline-3-one, and benzoyl peroxide is 40:20:20:10:3:4.4:0.6:2, and the particle size of the crushed construction waste is 5-10 mm.
[0097] Step 5: Pour the mixture into a mold, vibrate at 60 Hz for 10 minutes to flatten the mixture, and cure at 70°C for 2 hours to obtain ecological paving stones.
[0098] Comparative Example 2
[0099] This comparative example discloses a preparation process of ecological paving stones, comprising the following steps:
[0100] Step 1, EDTA and thionyl chloride are mixed, the molar ratio of EDTA to thionyl chloride is 1:8, react at 65°C until no gas is released, remove unreacted thionyl chloride by suction filtration, and dry in a vacuum drying oven at 50°C for 10 hours to obtain an EDTA chlorination product;
[0101] Step 2, disperse the EDTA chlorination product into N,N-dimethylformamide, the mass ratio of the EDTA chlorination product to N,N-dimethylformamide is 37:185, add ethylenediamine dropwise, the molar ratio of the EDTA chlorination product to ethylenediamine is 1:4, after the addition is completed, react at 90°C for 1.4h, after the reaction is completed, cool to room temperature, filter, add tetrahydrofuran 10 times the mass of the filtered precipitate to recrystallize the filtered precipitate, and place the crystalline product in a 50°C vacuum drying oven and dry for 10h to obtain an EDTA amidation product;
[0102] Step 3, dissolving copper nitrate in ethanol, wherein the mass ratio of copper nitrate to ethanol is 1:5, to obtain a copper nitrate solution;
[0103] The EDTA amidation product was added to ethanol, and after mixing, a copper nitrate solution was added, and the mass ratio of the EDTA amidation product, ethanol, and copper nitrate solution was 46:250:80. The mixture was stirred at room temperature and a stirring speed of 100 r / min for 2 h, and the ethanol was removed by rotary evaporation at a temperature of 50° C. to obtain a composite inhibitor;
[0104] Step 4: Mix the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyltriethoxysilane, and composite inhibitor, stir at a stirring speed of 200 r / min for 60 min, add benzoyl peroxide, and stir at a stirring speed of 200 r / min for 5 min to obtain a mixture;
[0105] The mass ratio of crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, γ-aminopropyl triethoxysilane, composite inhibitor, and benzoyl peroxide is 40:20:20:10:3:4.4:2, and the particle size of the crushed construction waste is 5-10 mm.
[0106] Step 5: Pour the mixture into a mold, vibrate at 60 Hz for 10 minutes to flatten the mixture, and cure at 70°C for 2 hours to obtain ecological paving stones.
[0107] In the above embodiments and comparative examples, fly ash was purchased from Jinchang Mineral Products Processing Plant in Lingshou County, grade: first class, particle size: 2000 mesh; unsaturated polyester is a liquid unsaturated polyester resin purchased from Yunfu Jiyi Chemical Co., Ltd., with a styrene content of 35%; bisphenol A epoxy resin is a liquid bisphenol A epoxy resin purchased from Guangzhou Korina New Materials Co., Ltd., model: E51.
[0108] Test example
[0109] The performance tests were conducted on the ecological paving stones prepared in the above embodiments and comparative examples:
[0110] (1) Moss growth inhibition performance test: The moss growth level of the ecological floor paving stone surface prepared in Examples 1-6 and Comparative Examples 1-2 was determined with reference to standard GB / T21353-2008. Level 0 means no growth, level 1 means trace growth (growth area S < 10%), level 2 means slight growth (growth area S is 10%-30%), level 3 means moderate growth (growth area S is 30%-60%), and level 4 means severe growth (growth area S ≥ 60%). The incubation time was 21 days. The test results are shown in Table 1:
[0111] Table 1
[0112]
[0113] As shown in Table 1, the ecological paving stone prepared by the present invention has good moss growth inhibition performance. 5-chloro-2-methyl-4-isothiazoline-3-one and copper ions are used as moss growth inhibition components, which can effectively inhibit the growth of moss. The copper ion chelating agent EDTA is modified. The amino and imino groups introduced during the modification process can participate in the curing of the epoxy resin, and the composite inhibitor is firmly combined with the binder in a chemically bonded manner, thereby improving the stability of the moss growth inhibition component in the paving stone, and the inhibition effect on moss is stable and lasting. Compared with Example 1, in Comparative Example 1, the EDTA amidation product and 5-chloro-2-methyl-4-isothiazoline-3-one are only physically mixed, and the EDTA amidation product and 5-chloro-2-methyl-4-isothiazoline-3-one are not connected by a chemical bond. During the curing process, 5-chloro-2-methyl-4-isothiazoline-3-one cannot be combined with the chelated copper with the binder by a stable chemical bond, the stability in the mixture is reduced, and the ability to inhibit the growth of moss is reduced. Compared with Comparative Example 1, in Comparative Example 2, 5-chloro-2-methyl-4-isothiazoline-3-one is not added, and the ability to inhibit the growth of moss is further reduced.
[0114] (2) Antibacterial performance test: The antibacterial rate of the ecological paving stones prepared in Examples 1-6 and Comparative Examples 1-2 was determined with reference to the standard QB / T4371-2012. The action time was 24 hours. The test results are shown in Table 2:
[0115] Table 2
[0116]
[0117] As can be seen from Table 2, the ecological paving stone prepared by the present invention has good antibacterial properties. 5-Chloro-2-methyl-4-isothiazoline-3-one and copper ions have excellent antibacterial properties as moss growth inhibitors. The copper ion chelator is modified and forms a quaternary ammonium salt during chemical bonding with 5-chloro-2-methyl-4-isothiazoline-3-one, which can further improve the antibacterial properties. Compared with Example 1, in Comparative Example 1, 5-chloro-2-methyl-4-isothiazoline-3-one and the EDTA amidation product are not connected by chemical bonds, the stability in the mixture is reduced, and the antibacterial ability is reduced; compared with Comparative Example 1, in Comparative Example 2, 5-chloro-2-methyl-4-isothiazoline-3-one is not added, and the antibacterial ability is further reduced.
[0118] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A preparation process of ecological paving stones, characterized in that: The steps include: Step 1, mixing EDTA and thionyl chloride, reacting, filtering and drying after the reaction is completed to obtain an EDTA chlorination product; Step 2, dispersing the EDTA chlorination product in N,N-dimethylformamide, adding ethylenediamine dropwise, reacting after the addition is complete, cooling after the reaction is complete, filtering, recrystallizing the filtered precipitate, and drying to obtain the EDTA amidation product; Step 3, dissolving 5-chloro-2-methyl-4-isothiazoline-3-one in ethanol to obtain a 5-chloro-2-methyl-4-isothiazoline-3-one solution; Dissolve copper nitrate in ethanol to obtain a copper nitrate solution; The EDTA amidation product is added to a 5-chloro-2-methyl-4-isothiazoline-3-one solution to react. After the reaction is completed, a copper nitrate solution is added, stirred, and rotary evaporated to obtain a composite inhibitor. Step 4: Mix the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, silane coupling agent, and composite inhibitor, stir, add a curing agent, continue stirring, and obtain a mixture; Step 5: Pour the mixture into the mold, vibrate and flatten it, heat and solidify it to obtain ecological paving stones.
2. A process for preparing the ecological paving stone according to claim 1, characterized in that: In the step 1, the molar ratio of EDTA to thionyl chloride is 1:(8-12), and the reaction is carried out at a temperature of 65-75° C. until no gas is released.
3. A process for preparing the ecological paving stone according to claim 1, characterized in that: In the step 2, the mass ratio of EDTA chlorination product to N,N-dimethylformamide is 37:(185-370), the molar ratio of EDTA chlorination product to ethylenediamine is 1:(4-5), and the reaction conditions are 90-100° C. for 1-1.4 hours.
4. A process for preparing ecological paving stones according to claim 1, characterized in that: In the step 3, the mass ratio of the EDTA amidation product, the 5-chloro-2-methyl-4-isothiazoline-3-one solution, and the copper nitrate solution is 46:(300-350):(80-100), the mass ratio of 5-chloro-2-methyl-4-isothiazoline-3-one to ethanol in the 5-chloro-2-methyl-4-isothiazoline-3-one solution is 1:(5-10), and the mass ratio of copper nitrate to ethanol in the copper nitrate solution is 1:(5-10).
5. A process for preparing ecological paving stones according to claim 1, characterized in that: In the step 3, the reaction conditions are 75-85° C. for 10-15 h, and the stirring conditions are 100-200 r / min for 1-2 h at room temperature.
6. A process for preparing ecological paving stones according to claim 1, characterized in that: In the step 4, the mass ratio of the crushed construction waste, fly ash, unsaturated polyester, bisphenol A epoxy resin, silane coupling agent, composite inhibitor and curing agent is (40-60):(20-30):(20-30):(10-20):(3-5):(5-10):(2-4).
7. A process for preparing ecological paving stones according to claim 1, characterized in that: In the step 4, the stirring condition is to stir at a stirring speed of 200-400 r / min for 30-60 min, and the condition for continuing stirring is to stir at a stirring speed of 200-400 r / min for 3-5 min.
8. A process for preparing ecological paving stones according to claim 1, characterized in that: The curing agent in step 4 includes benzoyl peroxide.
9. A process for preparing ecological paving stones according to claim 1, characterized in that: In the step 5, the vibration flattening condition is to vibrate at a frequency of 60-80 Hz for 5-10 minutes, and the heating curing condition is to cure at a temperature of 70-80° C. for 1-2 hours.
10. An ecological paving stone prepared by the preparation process of ecological paving stones according to any one of claims 1 to 9.
